Physical activity and its benefits on adolescents' mental health through self-esteem - Laurier, Catherine; Pascuzzo, Katherine; Jubinville, Vicky; Lemieux, Annie (Frontiers in Child and Adolescent Psychiatry, 2024)
BackgroundSince the onset of the COVID-19 pandemic, the scientific community has been concerned about the high rates of psychological distress among adolescents. The pandemic not only tested adolescents’ adaptation, but also disrupted key areas of their development. This demonstrates the need to study their psychological adjustment over time during this critical period to better guide services.ObjectiveThis study sought to explore the extent to which physical activity and its association with self-esteem in the first months of the pandemic impacted adolescents' psychological distress, six months later.MethodsTwo hundred and ninety-four adolescents (73% girls) between the ages of 12 and 17 participated in a longitudinal study launched at the start of the COVID-19 pandemic. The number of hours spent engaging in physical activity (HPA) in the past week and self-esteem were measured at Time 1 (T1; summer 2020). Psychological distress was measured at T1 and Time 2 (T2; winter 2021).ResultsMore HPA in the past week were related to greater self-esteem at T1. Greater self-esteem at T1 was related to lower psychological distress, six months later (T2). Lastly, HPA in the past week was not directly linked to psychological distress at T2, which confirms a fully indirect model.ConclusionResults suggest that physical activity is a key factor in promoting better mental health adjustment through its benefits in terms of self-esteem, even during times of turmoil. Findings reinforce the recommendation of promoting the practice of sports and athletic activity in difficult times.